Coxiella burnetii outbreak, Northern Italy 2021 - Annacarla Chiesa; Ciro Onza; Najada Sulcaj; Agate Torggler; Giulia Morosetti; Filippo Conforti; Elisabeth Kofler; Giacomo Moretto; Paola Sinigaglia; Liana Signorini; Christian Piffer; Maria Grazia Zuccaro; et al. (One Health, 2023)
Objective: We report an outbreak of 14 cases of Q fever among tourists caused by an infected calf and characterized by respiratory transmission and a high attack rate in humans. Materials and methods: Following the identification of an index case of Q fever in September 2021, an epidemiological investigation was conducted in collaboration with local Health and Veterinary authorities and an unknown outbreak was discovered and terminated. Results: The outbreak originated from the delivery by an infected cow, with spread of C. burnetii by air and infection via the respiratory route. The transmission period was calculated, and 25 potentially exposed tourists were identified: 14 were infected (56%) based on serological investigations, four were hospitalized, there were no deaths. All the 22 cows were tested by PCR for C. burnetii: 3 cows (14%) were positive on milk samples and one, the index animal, was also positive on blood. Conclusions: Timely diagnosis in a human patient was pivotal to identify the outbreak since involved animals were asymptomatic. The close collaboration between veterinary and human Public Health services in six different geographical areas of two countries was crucial for the rapid termination of the outbreak.